Analisis Tindakan Sexual Harassment Terhadap Kenyamanan Dan Produktivitas Kerja Karyawan (Studi Kasus Di PT. Fie Bandung) - Salsabila, Annisa Camelia; Rojak, Abdul (CV. ITTC INDONESIA, 2024)
This research is a case study of sexual harassment. Sexual harassment is a negative act that has a sexual context and can harm the victim physically and psychologically. This research used a quantitative method by distributing questionnaires to 50 respondents who worked at PT. FIE Bandung. By using the Sexual Experience Questionnaire (SEQ) questionnaire and participatory observation methods which allow researchers to feel and experience this phenomenon directly. This research aims to find out whether acts of sexual harassment (X) can affect employee comfort (Y1) and work productivity (Y2). This research was calculated using the SPSS version 27 program, from the results of the validity and reliability tests the three variables produced valid data, namely where r calculated > r table and reliable data where the Cronbach Alpha value was > 0.600. The results of this research also show that there is a relationship between acts of sexual harassment (X) on work comfort (Y1) of 24.3% and 11.3% on work productivity (Y2). The remainder is influenced by other variables not examined in this research. So it can be concluded that the author's hypothesis regarding sexual harassment can affect the comfort and work productivity of employees at PT. FIE Bandung has a positive and significant influence.